Studies on the function of two adjacent N6,N6-dimethyladenosines near the 3' end of 16S ribosomal RNA of Escherichia coli. IV. The effect of the methylgroups on ribosomal subunit interaction. - Poldermans, B (1980)
The effect of the presence or absence of the methylgroups of the m2(6)Am2(6)A sequence near the 3' end of 16S rRNA of Escherichia coli on the interaction of the ribosomal subunits has been studied, using wild-type (methylated) and mutant (unmethylated) ribosomes. Subunit exchange experiments and competitive association experiments show a strong preference of the 50S subunit for association with methylated 30S subunits. The results indicate that the equilibrium constant of the reaction 70S in equilibrium with 30S + 50S is dependent on the methylgroups; mutant 30S.50S couples are less stable than wild-type 30S.50S couples. It is postulated that the methylgroups also stimulate the interaction between 30S subunits and initiation factor IF-3.